Faktor Penyebab Kurangnya Minat Siswi SMP 08 Sawahunto Terhadap Olahraga Wushu - Nurmalina Nurmalina; Hermanzoni Hermanzoni (Performa, 2021)
The problem in this research is the interest of SMP 08 Kota Sawahlunto students in Wushu. The purpose of this study was to determine the causes of SMP 08 Kota Sawahlunto students to be less interested in Wushu. This study uses qualitative research with descriptive methods. This research produces descriptive data in the form of written or spoken words from people and observed behavior. The data collection techniques used were observation, interviews and documentation. This research was conducted from July to August 2020 at SMP 08 Sawahlunto City, Lumindai village, district. Barangin. The population in this study were 76 of all female students of SMP 08 Kota Sawahlunto. Sampling using proportional random sampling amounted to 15 students of SMP 08 Kota Sawahlunto. Based on the results of the research, the causes of the lack of asking students for Wushu consisted of two factors; 1) external factors and 2) internal factors. External factors, a) Infrastructure (27%), b) Distance (13%), c) Hard Wushu sports (20%), d) Parents (27%), e) Trainers (27%). Internal factors, a) Pain (7%), b) Lack of confidence (7%), c) Doubt (7%), d) Experience (7%)